Paralympic Games: the experience with “the other” trough screens - Augusto Moreira Marques; Antonio Luis Fermino; Doralice Lange de Souza (Journal of Physical Education (Maringá), 2020)
The International Paralympic Committee, institution that regulates  Paralympic sport, as well as some representatives of cities / countries that host the Paralympic Games claim that these Games are an important platform for changing perceptions of society regarding the capabilities of people with disabilities (PwD). Considering these allegations,  we developed a research that had as a goal to verify if individuals who had contact with the Paralympic Games changed their perception toward the abilities of PwD. The research was qualitative and exploratory. The data collection was based on semi-structured interviews conducted between April and July 2018. We interviewed 50 academics from different courses at Universidade Federal do Paraná (UFPR). We did a thematic analysis of the data and used the Intergroup Contact Theory (TCEG) for the discussion. The results of this work  reaffirm the TCEG thesis that postulates that both direct and indirect contact with distinct groups can serve as a tool to reduce prejudice.